Recursos didácticos en el proceso de cálculo y resolución de problemas de áreas de polígonos regulares, en décimo año de educación general básica en la unidad educativa “Ángel Polibio Cháves en el año lectivo 2023-2024 - Andrango, Mónica (2024)
The research was conducted with the purpose of determining the didactic resources in the process of calculus and problem solving of areas of regular polygons in tenth grade of EGB of the Angel Polibio Chavez Educational Unit, since students do not understand the teaching methods used by their teachers, which leads to lower academic performance, therefore, they tend to set limits because they do not understand mathematics, particularly calculus and problem solving. The research methodology has a qualitative-quantitative approach, with a descriptive, bibliographic and action research type of study, whose design was non-experimental and longitudinal, likewise, inductive, deductive, analytical and synthetic methods were used, where surveys and interviews were used as a technique to collect data, which were applied to 93 students from four parallels, subsequently, the information was processed in the statistical program SPSS and the mathematical software Geogebra. According to the results, it was possible to identify the difficulties that students have in learning regular polygons, as well as the didactic resources that are used in the educational establishment, in order to subsequently apply a proposal using appropriate didactic resources through the use of computer tools, concluding that the application of the Geogebra program allows improving the learning of regular polygons, as it is a novel and interactive tool